Evaluation of the Thermo Scientific™ SureTect™ Salmonella species Assay. (27th November 2019) - Cloke, Jonathan; Clark, Jr, Dorn; Radcliff, Roy; Leon-Velarde, Carlos; Larson, Nathan; Dave, Keron; Evans, Katharine; Crabtree, David; Hughes, Annette; Simpson, Helen; Holopainen, Jani; Wickstrand, Nina; et al.
Abstract: The Thermo Scientific™ SureTect™ Salmonella species Assay is a new real-time PCR assay for the detection of Salmonellae in food and environmental samples. This validation study was conducted using the AOAC Research Institute (RI) Performance Tested Methods SM program to validate the SureTect Salmonella species Assay incomparison to the reference method detailed in International Organization for Standardization 6579:2002 in a variety of food matrixes, namely, raw ground beef, raw chicken breast, raw ground pork, fresh bagged lettuce, pork frankfurters, nonfat dried milk powder, cooked peeled shrimp, pasteurized liquid whole egg, ready-to-eat meal containing beef, and stainlesssteel surface samples. With the exception of liquid whole egg and fresh bagged lettuce, which were tested in-house, all matrixes were tested by Marshfield Food Safety, Marshfield, WI, on behalf of Thermo Fisher Scientific. In addition, three matrixes (pork frankfurters, lettuce, and stainless steel surface samples) were analyzed independently as part of the AOAC-RI-controlled laboratory study by the University of Guelph, Canada. No significant difference by probability of detection or McNemars Chi-squared statistical analysis was found between the candidate or reference methods for any of the food matrixes or environmental surface samples tested during the validation study. Inclusivity and exclusivity testing was conducted with 117 and 36 isolates, respectively, which demonstrated that the SureTect Salmonella species Assay was able to detect all the major groups of Salmonella enterica subspecies enterica (e.g., Typhimurium) and the less common subspecies of S. enterica (e.g., arizoniae ) and the rarely encountered S. bongori . None of the exclusivity isolates analyzed were detected by the SureTect Salmonella species Assay. Ruggedness testing was conducted to evaluate the performance of the assay with specific method deviations outside of the recommended parameters open to variation (enrichment time and temperature, and lysis temperature), which demonstrated that the assay gave reliable performance. Accelerated stability testing was additionally conducted, validating the assay shelf life.